Ситуация на западных границах Боспорского царства в конце IV – III вв. до н.э. (по материалам монетных находок) - Терещенко, А.Е. (Боспорские исследования, 2009)
The political situation on the land of the remote chora of Theodossia in the end of the 4th- the first half of the 3rd century BC is examined in the article. Several stages can be singled out after mapping of Bosporus coins found on this territory by chance. Each monetary type has its area of circulation.